Pendampingan Pemanfaatan Media Sosial dalam Peningkatan Promosi Desa Wisata Bongan Kabupaten Tabanan Bali - Diwyarthi, Ni Desak Made Santi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
Bongan Village is a potential tourist village facing challenges such as limited infrastructure, low tourist visits, dependence on the government, and a lack of human resources. The community service program helps village members explore their potential, enhance their competencies, and utilize digital marketing strategies. A total of 20 village youths participated in the community service program held in August 2023. The program aims to foster village development through socialization, training, and monitoring. Objectives encompass ensuring tourism operations run smoothly, empowering locals as tourism contributors, enhancing the village's appeal to tourists, boosting visitor numbers, and elevating community income. This Community Service Program complies with Indonesia's National Education System Law and unfolds in three phases: socialization, training, and monitoring, propelling Bongan Village toward self-sustaining tourism growth.